洛神与人神恋母题在戏曲中定型与演化: The Canonization and Development of the Luoshen Imagery and the Human-God Romance Motif in Chinese Theatrical Tradition - Shu Zi Qin , Teoh Hooi See 舒子芩，张惠思 (Journal of Sinological Studies 漢學研究學刊, 2024)
洛神自先秦起便是文学作品中不可方物的神女形象，她既是楚辞中无具体形象描绘的寄托之物，又是辞赋里翩若惊鸿的“斯水之神”，还是戏曲中甄后神魂化的洛水之神，经历了不断的传承和演变。从明杂剧《洛水悲》到清杂剧《凌波影》，再到梅派京剧《洛神》，宓妃与曹植间的爱情故事延续了人神恋母题的框架和文旨传统，不断塑造人物、细化情节、创新表演，使洛神的中心意象和人神恋母题在戏曲中得以定型与延续。戏曲中人神恋的描写常体现出当时关于性别等级与婚姻规范的社会讨论，一方面体现出超越现实束缚的浪漫想象，另一方面也暗含对突破既定社会秩序的焦虑。 Since the pre-Qin period, the goddess Luoshen has been portrayed as an ethereal and transcendent figure in Chinese literature. In the Chuci, she embodies abstract longing without a concrete form; in Han rhapsodies, she emerges as the goddess of the Luo River, “graceful as a startled swan”; and in traditional drama, she becomes the deified spirit of Empress Zhen. Her image has been continually reinterpreted through works like the Ming zaju Luoshui Bei, the Qing zaju Lingbo Ying, and the Mei school Peking opera Luoshen, all of which preserve the romantic narrative between the goddess Fufei and Cao Zhi. These performances refine characterization, expand plotlines, and innovate theatrical techniques, reinforcing Luoshen’s imagery and the motif of human-divine love. Such romances reflect both idealized transcendence of worldly constraints and implicit anxieties about disrupting social and moral norms, making the human-divine romance a means of aesthetic expression and a lens for negotiating sociocultural tensions.